Implementasi Strategi Influencer Marketing untuk Membangun Brand Awareness di Industri Skincare Pria - Adireja, Muhamad Husni; Barkah, Cecep Safa’atul; Novel, Nurillah Jamil Achmawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The purpose of this study is to look into how influencer marketing techniques affect brand awareness in the men's skincare market. The method used is a literature review that examines relevant literature from scientific journals, using keywords such as